2018
DOI: 10.1186/s12902-018-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control for people with type 2 diabetes in Saudi Arabia – an urgent need for a review of management plan

Abstract: BackgroundThe aim of this study was to assess inadequate glycaemic control and its associated factors among people with type 2 diabetes in Saudi Arabia.MethodsA cross-sectional study design was used. Adults with type 2 diabetes attending diabetes centres in Riyadh, Hofuf and Jeddah cities were interviewed and their anthropometrics were measured. Their medical records were also reviewed to collect information related to recent lab tests, medications, and documented comorbidities. Multivariable logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
71
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 57 publications
14
71
4
Order By: Relevance
“…For the majority of patients, a healthy diet is related to the high-level consumption of carbohydrates, whereas for others high protein must be consumed to control the effect and level of diabetes. Alramadan et al [6] demonstrated that the majority of the people were prone to unhealthy lifestyles leading towards other healthrelated issues such as obesity. This has provided them greater difficulties in controlling their sugar and blood levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of patients, a healthy diet is related to the high-level consumption of carbohydrates, whereas for others high protein must be consumed to control the effect and level of diabetes. Alramadan et al [6] demonstrated that the majority of the people were prone to unhealthy lifestyles leading towards other healthrelated issues such as obesity. This has provided them greater difficulties in controlling their sugar and blood levels.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes in developing countries is relatively high. In fact, Saudi Arabia as a developing country has the highest diabetes prevalence in both regional and global landscapes [6]. The state invested about 1,142 million dollars for overcoming the progressive disease in the country which is tremendously affecting its workforce.…”
Section: Introductionmentioning
confidence: 99%
“…About three-fourths of participants had inadequate glycaemic control (≥ 7%). Multivariable analysis showed that age ≤ 60 years, longer duration of diabetes, low household income, low intake of fruits and vegetable, low level of physical activity, high waist-hip ratio, low adherence to medication, and using injectable medications were independent risk factors for inadequate glycaemic control [16]. Among 480 subjects with self-reported diabetes in Phase I of INDIAB (2008 -2010), good glycemic control (HbA1c <7%) was observed only in 31.1% of urban and 30.8% of rural subjects.…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%
“…Cohen et al [191] Alramadan et al [167] Saudi Arabia, the US Low number of complications Bailey et al [189], Rolnick et al [181] Jamous et al [192], Palestine, the US…”
Section: Medical -Related Long Duration Of Diabetesmentioning
confidence: 99%